2021
DOI: 10.48550/arxiv.2111.07252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsic first and higher-order topological superconductivity in a doped topological insulator

Harley D. Scammell,
Julian Ingham,
Max Geier
et al.

Abstract: We explore higher order topological superconductivity in an artificial Dirac material with intrinsic spin-orbit coupling, which is a doped Z2 topological insulator in the normal state. A mechanism for superconductivity due to repulsive interactions -pseudospin pairing -has recently been shown to naturally result in higher-order topology in Dirac systems past a minimum chemical potential [1].Here we apply this theory through microscopic modeling of a superlattice potential imposed on an inversion symmetric hole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 90 publications
(188 reference statements)
0
7
0
Order By: Relevance
“…Unlike the p-wave states, the s-wave state is protected against the effects of weak disorder by a generalized Anderson's theorem, so this state might posses a higher T c than the topological phases in a sufficiently disordered system. In a separate study, we also suggest that these two phases may arise due to spin-orbit coupling and study their properties in detail [71].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Unlike the p-wave states, the s-wave state is protected against the effects of weak disorder by a generalized Anderson's theorem, so this state might posses a higher T c than the topological phases in a sufficiently disordered system. In a separate study, we also suggest that these two phases may arise due to spin-orbit coupling and study their properties in detail [71].…”
Section: Discussionmentioning
confidence: 84%
“…This phase possesses a Chern number which leads to a gapless, anomalous edge spectrum. In a separate study, we show that this phase may become dominant when spin orbit coupling is present, and analyze the topology of this phase in detail [71].…”
Section: Topological Edge and Corner Modesmentioning
confidence: 94%
“…First principles calculations could relate our phase diagram to these experiments by determining δ, µ and couplings as a function of pressure. Variation of doping and pressure indicates the presence of two distinct superconducting phases [46][47][48]; it is possible that the TvHS dominates the physics in one doping regime, while other interaction physics could be important elsewhere in the phase diagram [82][83][84][85][86][87]-e.g. it has been shown that sublattice interference near the K-points can result in higher-order topological multigap s-or p-wave states [11,86,87].…”
Section: Discussionmentioning
confidence: 99%
“…The question was addressed by considering the effect of Coulomb repulsive interactions [19][20][21] and/or by developing a number-conserving theory [22] in order to go beyond the BCS approximation. In particular, some recent studies investigated the physical properties of HOTSCs when Coulomb interactions are taken into account [23,24].…”
Section: Introductionmentioning
confidence: 99%